2022
DOI: 10.1186/s12933-022-01546-0
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the triglyceride-glucose index and risk of cardiovascular diseases and mortality in the general population: a systematic review and meta-analysis

Abstract: Background The triglyceride-glucose (TyG) index is a new alternative measure for insulin resistance. This meta-analysis was conducted to assess the associations of the TyG index with the risks of cardiovascular diseases and mortality in the general population. Methods The PubMed, Cochrane Library and Embase databases were searched for randomized controlled trials or observational cohort studies reporting associations of the TyG index with cardiovas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
95
0
10

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(108 citation statements)
references
References 72 publications
3
95
0
10
Order By: Relevance
“…Similarly, the TyG index only appeared to be associated with cardiovascular risk in nondiabetes patients. Some previous studies have indicated that the TyG index could predict cardiovascular events effectively both in patients with and without DM [33][34][35], but a study has found similar associations in diabetic populations but not in nondiabetic populations [36]. In this study, we assumed that this was mainly because the insufficient sample size in the DM group led to decreased test efficiency.…”
Section: Discussionmentioning
confidence: 80%
“…Similarly, the TyG index only appeared to be associated with cardiovascular risk in nondiabetes patients. Some previous studies have indicated that the TyG index could predict cardiovascular events effectively both in patients with and without DM [33][34][35], but a study has found similar associations in diabetic populations but not in nondiabetic populations [36]. In this study, we assumed that this was mainly because the insufficient sample size in the DM group led to decreased test efficiency.…”
Section: Discussionmentioning
confidence: 80%
“…Several previous studies have reported that a high TyG index is related to the increased risk of cardiovascular disease and all-cause mortality in the general population. A recent meta-analysis included 5 studies for composite cardiovascular disease with 259,757 participants and found higher TyG index may be associated with an increased incidence of CVD in a linear association among the general population [ 26 ]. The pooled HRs (95% CI) for CVD among those with the highest TyG index was 1.46 (1.23–1.74) when compared with the lowest TyG index category.…”
Section: Discussionmentioning
confidence: 99%
“…Although the influence of the TyG index on adverse health outcomes has been receiving increasing attention, studies evaluating the relationship between the TyG index and mortality have been limited. In the recent meta-analysis of the TyG index and the risk of mortality in the general population [ 26 ], their results showed no association between the TyG index and mortality or all-cause mortality. In fact, among the four studies they included, two found a statistically significant association between the TyG index and all-cause mortality [ 30 , 31 ], while the other two did not [ 28 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies(16-34) and our recent work (35) have reported a signi cant association between the TyG index and the incidence of atherosclerosis, myocardial infarction (MI), stroke, coronary artery disease and mortality in the general population regardless of T2DM status. Furthermore, the TyG index is associated with adverse cardiovascular events among diabetic or nondiabetic patients with established cardiovascular diseases (CVDs) (36)(37)(38)(39)(40)(41)(42).…”
Section: Introductionmentioning
confidence: 89%